Adapting a Remote Laboratory Architecture to Support Collaboration and Supervision - Lowe, David; Berry, Chris; Murray, Steve; Lindsay, Euan (International Journal of Online and Biomedical Engineering (iJOE), 2009)
Interest in, and use of, remote laboratories has been rapidly growing. These laboratories provide remote access, via the internet, to real laboratory equipment. Under appropriate circumstances they can support or even replace traditional (proximal) laboratories, provide improved access at reduced cost, and encourage inter-institutional sharing of expensive resources. Most attention to date has been on the development of the core infrastructure that manages access and interaction, and to a lesser extent consideration of pedagogic issues such as which learning outcomes are best suited to this modality. There has however been a recent recognition of the importance of also considering how collaboration and supervision can also be supported. In this paper we discuss a novel approach to the integration of support for multi-user distributed access to a single laboratory instance. The approach retains the benefits of the lightweight client inherent in the underlying architecture.